CARE OF SOULS AND THE LOGIC OF TRENT AS A PASTORAL COUNCIL - V.U. Iheanacho (Acta Theologica)
The Council of Trent (1545-1563) is often depicted as being primarily concerned with the promulgations and reaffirmations of traditional doctrines. It is equally perceived to have churned out dogmas and the enunciations of anathemas on those whose Christian beliefs and practices were considered deviations from orthodox teachings and practices of the faith. This article is a departure from such straitjacketing about Trent. Its overall objective is to shed light on Trent as predominantly a pastoral council.